1992
DOI: 10.1007/bf01204051
|View full text |Cite
|
Sign up to set email alerts
|

Embryo density and medium volume effects on early murine embryo development

Abstract: Our results suggest that a stimulatory interaction occurs among embryos possibly exerted through the secretion of growth factors. This effect can be diluted if the embryos are cultured in large drops or singly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 6 publications
2
25
0
1
Order By: Relevance
“…Although some reports indicated that mammalian embryos cultured in groups exhibit better embryonic development than those cultured singly [1][2][3][4], it remains unclear by what mechanism group culture promotes embryonic development in vitro. It has been postulated that embryos secrete certain growth factors as embryonic autocoids to support or promote their development in vitro [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although some reports indicated that mammalian embryos cultured in groups exhibit better embryonic development than those cultured singly [1][2][3][4], it remains unclear by what mechanism group culture promotes embryonic development in vitro. It has been postulated that embryos secrete certain growth factors as embryonic autocoids to support or promote their development in vitro [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…It has been postulated that embryos secrete certain growth factors as embryonic autocoids to support or promote their development in vitro [5][6][7][8][9][10]. Group culture with different numbers of embryos in different volumes of culture medium resulted in differential embryonic development in vitro [2,3,11]. Therefore, the volume of micro-drop (culture medium) or density of embryos is an important factor for embryonic development in vitro.…”
Section: Introductionmentioning
confidence: 98%
“…However, for commercial purposes such as use in OPU, where it is usually necessary just to keep the immature oocytes from one donor together, a small number of oocytes/embryos can be cultured (approximately three to six oocytes recovered per nonstimulated cow; Rizos et al, 2005;Chaubal et al, 2006). It has been widely reported that in vitro embryo development in bovine and other mammalian species tends to be suppressed in cultures with a single or low number of embryos (in mouse: Paria and Dey, 1990;Canseco et al, 1992;Lane and Gardner, 1992;Kato and Tsunoda, 1994;in bovine: Palma et al, 1992;Ferry et al, 1994;Keefer et al, 1994;Blondin and Sirard, 1995;Carolan et al, 1996;Donnay et al, 1997;O'Doherty et al, 1997;Ward et al, 2000;Pereira et al, 2005;Fujita et al, 2006). It seems that the culture systems developed to culture embryos in groups could be unsuitable and/or incomplete for individual embryo culture, and there must be some kind of limiting factor or condition in single embryo in vitro culture systems which remain still without knowing (Nagao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While cell types requiring longer attachment times may need a larger drop volume to prevent hypoxia, previous studies have shown that embryos cultured in a 5 l drop volume under silicone oil remain viable after 120 h. 21 Mineral oil was selected for all further cell-seeding experiments. Silicone oil was omitted due to its strong adsorption to exposed silanol groups on glass surfaces.…”
Section: B Cell Attachmentmentioning
confidence: 99%